Comparison of two coarse-grained models of cis-polyisoprene with and without pressure correction. (9th November 2017) - Ohkuma, Takahiro; Kremer, Kurt
Abstract: We investigate two coarse-grained models of a cis -polyisoprene melt. The bonded interactions which are used in both models are derived by Boltzmann inversion of the probability distributions of the bonded variables in a single chain simulation. The non-bonded interactions are derived by an iterative Boltzmann inversion method in the melt state with pressure correction in a model and without in the other model. In our mapping rule, two or three carbons are grouped into coarse-grained beads. The trade-off relationship between pressure and compressibility is observed in the coarse-grained models. Since the relaxation dynamics of the coarse-grained models are accelerated by the smoothed potentials, single numerical factors are introduced to rescale the time scale of the coarse-grained models, respectively. The factors of the two models are in the same order but the model with pressure correction displays larger acceleration than the other. It is found that the stress relaxation function near equilibrium and the nonlinear viscosity under steady shear are essentially the same between the two coarse-grained models in the rescaled time scales despite of their different equilibrium pressures. We also study the dependency of the rescaling factors on the chain length of the polymer. The rescaling factors increase with increasing the chain length and exponentially saturates to certain values around 100 monomers in chains. Graphical abstract: Highlights: Equilibrium pressure and compressibility are different in the two models. Two models show the same Kuhn length and entanglement molecular weight. Two models show the same stress relaxation function and viscosity.